Institutional information technology heritage: Analysis of the case of El Museíto de la EESTN3 - Bianculli, Karina (2024)
The paper presents the results of an extension university project entitled “Tecno-History MDQ II. The Museíto informático de la EESTN3” promotes the construction of a small historical-educational museum of national informatics with artefacts that are oriented to school audiences and the general public. These artefacts are considering as a pedagogical device, with the aim to recover his value. In this extension project, at least three sets of problems were addressed: the discussions and actions regarding the heritage activation of computer artefacts; the link between the academic debate on the history of national computing, its teaching and public communication; and, finally, the intersection between history, memory and heritage processes in the framework of the democratisation of knowledge about computing.